STRATEGI COPING ORANGTUA YANG MEMPUNYAI ANAK DENGAN DISORDERS OF SEX DEVELOPMENT KROMOSOM SEKS MOSAIK - Fitrianingrum, Iit; Ediati, Annastasia; Faradz, Sultana MH (Faculty of Psychology, Diponegoro University, 2018)
This study aims to explore coping strategies used by parentsâ€™ of children with mosaic sex chromosome Disorders of Sex Development (DSD). The study applied the sequential explanatory mixed-methods approach that collected quantitative data prior to qualitative data.Â Participants were parents of the affected patients diagnosed with DSD with the following karyotype XX/XY, X/XY, XYY, or XXY variants. In total, 14 mothers and 12 fathers of 14 patients with a mosaic sex chromosome DSD participated in this study. We used the Indonesian version of BRIEF COPE to collect quantitative data on coping strategies. Furthermore, an invidual interview was conducted to all participants to elaborate the coping strategies applied by parents in raising their children. The data analysis identified the four most preferred parental coping strategies: Â religion, positive reframing, acceptance, and active coping whereas the least preferred coping strategies were humor, substance use, and behavior disengagement. Mothers and fathers in the study did not significantly differ in applying their coping strategies (p>.05). The study suggests health practitioners working with parents of patients affected with mosaic sex chromosome DSD to promote the religion, positive reframing, acceptance, and active coping strategies to facilitate a better acceptance of the affected children.